2019
DOI: 10.1103/physrevb.100.184402
|View full text |Cite
|
Sign up to set email alerts
|

Layer-dependent spin-orbit torques generated by the centrosymmetric transition metal dichalcogenide βMoTe2

Abstract: Single-crystal materials with sufficiently low crystal symmetry and strong spin-orbit interactions can be used to generate novel forms of spin-orbit torques on adjacent ferromagnets, such as the out-of-plane antidamping torque previously observed in WTe 2 /ferromagnet heterostructures.Here, we present measurements of spin-orbit torques produced by the low-symmetry material β-MoTe 2 , which unlike WTe 2 retains bulk inversion symmetry. We measure spin-orbit torques on β-MoTe 2 /Permalloy heterostructures using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 50 publications
5
50
1
Order By: Relevance
“…Previous studies of SOT based on 2D materials have been reported in semiconducting MoS 2 and WSe 2 , [ 23,24 ] metallic NbSe 2 , [ 25 ] semimetallic WTe 2 , [ 26–28 ] and MoTe 2 . [ 29,30 ] Especially, the novel observations of out‐of‐plane spin induced anti‐damping torque in WTe 2 and MoTe 2 hold a great promise for field‐free switching of the perpendicularly magnetized system. However, a direct demonstration of SOT‐induced magnetization switching utilizing a 2D material is still at its infancy and the thickness‐dependence of SOTs in 2D materials is not well understood.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of SOT based on 2D materials have been reported in semiconducting MoS 2 and WSe 2 , [ 23,24 ] metallic NbSe 2 , [ 25 ] semimetallic WTe 2 , [ 26–28 ] and MoTe 2 . [ 29,30 ] Especially, the novel observations of out‐of‐plane spin induced anti‐damping torque in WTe 2 and MoTe 2 hold a great promise for field‐free switching of the perpendicularly magnetized system. However, a direct demonstration of SOT‐induced magnetization switching utilizing a 2D material is still at its infancy and the thickness‐dependence of SOTs in 2D materials is not well understood.…”
Section: Figurementioning
confidence: 99%
“…From experiments, we extract the SHC of ≈250 (ℏ /e ) Ω −1 cm −1 , which is similar to the value of ≈280 (ℏ /e ) Ω −1 cm −1 reported by Safeer et al., [ 30 ] but larger than the previously reported value of ≈29 (ℏ /e ) Ω −1 cm −1 . [ 29 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Thickness dependent ST-FMR measurements on NbSe 2 (1-10 layers)/Py heterostructures revealed an in-plane DL torque τ y e with a torque conductivity (σ y e 3 × 10 3 (Z/2e)(Ωm) − 1 ) comparable to other TMD/Py heterostructures and observable down to a monolayer of NbSe 2 (Guimarães et al, 2018). Similar to β-MoTe 2 /Py (Stiehl et al, 2019a), τ y e shows only a weak thickness dependence.…”
Section: Metallic Tmdsmentioning
confidence: 57%
“…Another interesting semi-metallic TMD is β-MoTe 2 which, different than WTe 2 and similar to TaTe 2 , possess inversion symmetry in its bulk form. Using β-MoTe 2 /Py bilayers Stiehl et al observe the presence of an out-of-plane DL torque τ z e using ST-FMR measurements (Stiehl et al, 2019a). This is allowed by the inversion symmetry breaking at the β-MoTe 2 /Py interface and indicates that inversion asymmetry in the bulk is not a strict requirement for τ z e to be observed.…”
Section: Semi-metallic Tmdsmentioning
confidence: 99%